Aplikasi Perangkat Ajar “Petualangan Fisika” Berbasis Multimedia untuk SMP Kelas 8 - Fredy Purnomo; Silviana Simidjaja; Dwi Pangestuti; Anggondo Paulus Stifanus (Bina Nusantara University, 2011)
Multimedia can be used as a supportive element in education. The most significant implementation of multimedia is shown in computer assisted instruction (CAI). It is a self-instructional program which provides an accessible, interactive, and flexible way of presenting curriculum material. Therefore, this research objective is to design and develop a CAI for physics as a supportive learning method at school. Interactive Multimedia System Design & Development Cycle is used as the research method. It explains about a development and design cycle, especially for interactive multimedia system. Any information and data for analyzing user's need are obtained through questionnaire and interview. From the research, it is shown that most of the students face difficulties in learning physics as they imagine the logic or process that happens. Being implemented, most students as well as teachers are interested in this application that makes it easier for them to understand the physics process.